SOME ASPECTS OF IMPROVING PHYSICS TEACHING IN MILITARY HIGHER EDUCATION INSTITUTIONS USING ARTIFICIAL INTELLIGENCE (International Educators Conference, 2025)
This article examines in detail various aspects and possibilities for improving the teaching of physics in military higher education institutions using artificial intelligence technologies, which analyzes in detail the impact of artificial intelligence-based tools on the effectiveness of cadets mastering this discipline, as well as the role they play in supporting teachers' approaches. Based on experimental methods and the results of statistical analysis, it will be proved that the integration of artificial intelligence into the educational process significantly improves learning outcomes, which once again confirms the relevance of using these technologies in the modern education system. As a result of the research, specific and useful recommendations have been developed for the implementation of educational technologies based on artificial intelligence in higher education institutions.